Asymmetric biomimetic transamination of α-keto amides to peptides - Weiqi Cai (Nature Portfolio, 2021)
Asymmetric transamination of α-keto amides could provide an efficient strategy to synthesise peptides, but has not been well developed yet. Here, the authors design chiral pyridoxamine catalyst and realize the asymmetric biomimetic transamination of α-keto amides, providing access to various peptides with excellent enantiopurities.